Measurement and determinants of rural food poverty in Nigeria: recent evidence from general household survey panel - Jabo, Mohammad Sani Muhammad; Ismail, Mohd Mansor; Abdullah, Amin Mahir; Shamsudin, Mad Nasir (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2017)
This paper examines food security determinants among rural farming households in Nigeria. A total of 3380 households from General Household Survey-panel data that adopt the World Bank Living Standard Measurement Survey (LSMS) technique was used for this study. The impacts of household characteristics, household endowments and activity related characteristics were explored using logistic regression analysis. Based on the Food and Agriculture Organization FAO recommended minimum 2120 kcal daily per adult equivalent was valued at (N138) equivalent and USD 0.87 food poverty threshold of per annum was derived for rural Nigeria. This threshold is the cost for purchasing recommended daily food allowances (RDA) of an adult equivalent for healthy life in rural Nigeria. The results of the study revealed that age of the household head, tertiary education, farm size, household size, value of livestock holdings, total remittances received by the household, participation in nonfarm enterprise and access to formal credit have significant impact on food security. We conjecture that, the higher incidence of food security during post harvesting season might likely be due to inability of smallholder farmers to utilize their extra time into non-farm income generating activities due to high demand for labour for farm operations.